The effects of home-based primary care on Medicare costs at Spectrum Health/Priority Health (Grand Rapids, MI, USA) from 2012-present: a matched cohort study - Stephen A. Stanhope; Mary C. Cooley; Linda F. Ellington; Gregory P. Gadbois; Andrew L. Richardson; Timothy C. Zeddes; Jay P. LaBine (BMC, 2018)
Abstract Background In the United States, home-based primary care (HBPC) is increasingly proposed as a means of enabling frail elders to remain at home for as long as possible, while still receiving needed medical care. However, there are relatively few studies of either the medical outcome effects or cost benefits of HBPC. In this paper, we examine medical cost and mortality outcomes for enrollees in the HBPC program offered by Spectrum Health/Priority Health (SH/PH), a not-for-profit integrated health care/health insurance system located in Grand Rapids, MI, USA. Methods We perform a concurrent matched cohort study. SH/PH HBPC enrollees during 2012-2014 are matched for prior costs, age, sex and comorbidities against controls selected from unenrolled insurance plan members. Twelve and twenty four-month medical costs are compared between HBPC participants and matched controls, overall and conditional on mortality status. Mortality rates of HBPC participants are studied on their own and in comparison to controls. Results At 12 and 24 months, in comparison to matched controls HBPC participants show higher ($2933) and lower ($8620) costs respectively. Relative costs and savings of HBPC participants are a function of short term increased costs upon entry into the program (enrollees who survive the first year cost $5866 more than controls); substantial savings at end-of-life (approximately $37,037 in savings relative to controls are realized); and the overall mortality of HBPC participants (mean residual lifespan is 37.75 months from the time of enrollment). We project the present value of lifetime medical cost savings due to enrollment in the HBPC program to be at least $14,336. Conclusions The SH/PC HBPC program reduces healthcare costs while enabling frail elders to remain at home. Reduction in costs is obtained at end-of-life and is offset with a smaller initial increase in costs upon enrollment.